HUBUNGAN LAMA PENGGUNAAN KONTRASEPSI SUNTIK 3 BULAN DENGAN PENINGKATAN BERAT BADAN AKSEPTOR KB DI PRAKTEK MANDIRI BIDAN ARTA PEKANBARU - Septia, Qori Armiza; Hayati, Iznirrahma; Luthfiyah, Ummu; Gandi, Putri Indra; Susanti, Evi (Ensiklopedia of Journal, 2025)
Abstract: The family planning (KB) program aims to regulate the birth of children, the distance between births, and the ideal age for giving birth through promotion, protection, and assistance according to reproductive rights to create quality families (BKKBN, 2015). One of the birth control methods is the 3-month injectable contraceptive, which is effective and long-acting (Affandi, 2013). This study aims to determine the relationship between the duration of using injectable contraception for 3 months and the increase in weight of acceptors at the Independent Practice of Midwife Arta Pekanbaru. The method used is an analytical survey with a cross-sectional approach to explore this phenomenon. The research population was all 3-month injection acceptors at that place, namely 115 people, with a sample of 89 respondents taken by accidental sampling. Data was collected using a checklist sheet from the respondent's family planning card and analyzed by distribution using the chi-square test and obtained a p-value = 0.003. The results of the chi-square test showed a significant value (p-value = 0.003<0.05), indicating a relationship between the duration of using injectable contraception for 3 months and an increase in the acceptor's weight. Therefore, it is recommended that midwives provide education regarding the side effects of 3-month contraceptive injections, especially an increase in body weighKeywords: Injectable Contraception, Use of Injectable Birth Control, Weight Gain